Postoperative Pulmonary Complications' Association with Sugammadex versus Neostigmine: A Retrospective Registry Analysis. (17th March 2021) - Li, Gen; Freundlich, Robert E.; Gupta, Rajnish K.; Hayhurst, Christina J.; Le, Chi H.; Martin, Barbara J.; Shotwell, Matthew S.; Wanderer, Jonathan P.
Abstract : Background: Postoperative residual neuromuscular blockade related to nondepolarizing neuromuscular blocking agents may be associated with pulmonary complications. In this study, the authors sought to determine whether sugammadex was associated with a lower risk of postoperative pulmonary complications in comparison with neostigmine. Methods: Adult patients from the Vanderbilt University Medical Center National Surgical Quality Improvement Program database who underwent general anesthesia procedures between January 2010 and July 2019 were included in an observational cohort study. In early 2017, a wholesale switch from neostigmine to sugammadex occurred at Vanderbilt University Medical Center. The authors therefore identified all patients receiving nondepolarizing neuromuscular blockades and reversal with neostigmine or sugammadex. An inverse probability of treatment weighting propensity score analysis approach was applied to control for measured confounding. The primary outcome was postoperative pulmonary complications, determined by retrospective chart review and defined as the composite of the three postoperative respiratory occurrences: pneumonia, prolonged mechanical ventilation, and unplanned intubation. Results: Of 10, 491 eligible cases, 7, 800 patients received neostigmine, and 2, 691 received sugammadex. A total of 575 (5.5%) patients experienced postoperative pulmonary complications (5.9% neostigmine vs . 4.2% sugammadex). Specifically, 306 (2.9%) patients had pneumonia (3.2% vs . 2.1%), 113 (1.1%) prolonged mechanical ventilation (1.1% vs . 1.1%), and 156 (1.5%) unplanned intubation (1.6% vs . 1.0%). After propensity score adjustment, the authors found a lower absolute incidence rate of postoperative pulmonary complications over time (adjusted odds ratio, 0.91 [per year]; 95% CI, 0.87 to 0.96; P < .001). No difference was observed on the odds of postoperative pulmonary complications in patients receiving sugammadex in comparison with neostigmine (adjusted odds ratio, 0.89; 95% CI, 0.65 to 1.22; P = 0.468). Conclusions: Among 10, 491 patients at a single academic tertiary care center, the authors found that switching neuromuscular blockade reversal agents was not associated with the occurrence of postoperative pulmonary complications. Abstract : At a medical center that implemented a complete switch from neostigmine to sugammadex, a statistically significant difference in pulmonary complication rates was not observed between 7, 800 general surgery patients receiving neostigmine versus 2, 691 general surgery patients receiving sugammadex. Although rates of pulmonary complication after general surgery are decreasing, some of this change may be attributable to temporal trends in practice unrelated to the use of neostigmine versus sugammadex. Supplemental Digital Content is available in the text.